REACTION OF THE ADRENAL GLANDʼS MICROCIRCULATION WITH ACUTE ASEPTIC PERITONITIS - Shepitʼko, V.I.; Skotarenko, T.A. (World of Medicine and Biology, 2015)
Adrenal glands have functions necessary for normal activity of a man. Studying of changes in tissues of these glands during peritonitis. enables to work out new methods of treatment of inflammatory diseases of abdominal cavity and to determine the contribution of adrenal glands in inflammation development and struggle with it.
Keywords: adrenal glands; microcirculation; peritonitis; aseptic inflammation